Efficacy of Narrow-Band Ultra Violet B versus Narrow-Band Ultra Violet B with Topical Tacrolimus Ointment (0.1%) in the Treatment of Vitiligo (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Several treatment options e.g. topical corticosteroids, phototherapy like narrow-band ultra violet B (NB-UVB) and psoralen+ultra violet A (PUVA) etc are available for vitiligo. But none is so effective in single but combined one is more effective and superior.Objective: To compare the efficacy of NB-UVB vs NB-UVB with topical Tacrolimus ointment (0.1%) in the treatment of Vitiligo.Materials and Methods: This descriptive cross-sectional study was conducted in Combined Military Hospital, Dhaka from October 2015 to April 2016. Total 100 patients with vitiligo were divided into 2 groups of 50 patients. NB-UVB was given for 04 weeks to Group-A. In Group-B patients, topical Tacrolimus ointment (0.1%) twice daily was advised with simultaneous NB-UVB. The patients were followed-up at the baseline of the 4th, 8th and 16th week.Results: Majority (46%) of the patients were from 25-34 years of age with a mean age of 27.4±12.6 years. Among all risk factors, Family history of Vitiligo was the most common risk factor and common skin type (Fitzpatrick) was Type IV (40%). At the end of 4th week, maximum cases of Group-B showed good response (score 3) with a mean score of 1.74. Whereas, maximum cases of Group-A showed poor response (score 1) with a mean score of 0.86. End of the 16th week, maximum cases of Group-B improved successfully. In the end, 20% patients of Group-A showed an excellent result; but it was 42% from Group-B.Conclusion: It is revealed from this study that patients treated with a combination of NB-UVB with topical Tacrolimus ointment (0.1%) showed better treatment outcome, more effective and becomes a new mode of treatment.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 86-89